A non-covalent strategy to prepare electron donor-acceptor rotaxanes - Scarel, Francesco; Ehli, Christian; Guldi, Dirk Michael; Mateo-Alonso, Aurelio (Chemical Communications, 2013)
A straightforward non-covalent synthetic strategy for producing donor-acceptor rotaxanes is reported. Femtosecond absorption spectroscopy illustrates that the use of this strategy gives rise to supramolecular chromophores with different electron transfer behavior. © 2013 The Royal Society of Chemistry.

A three-level luminescent response in a pyrene/ferrocene rotaxane - Mateo-Alonso, Aurelio; Ehli, Christian; Guldi, Dirk Michael; Prato, Maurizio (Organic Letters, 2013)
A solvent switchable rotaxane equipped with a pyrene stopper and with two ferrocenyl units on the macrocycle is reported, in which three different states, two nondegenerate and one degenerate, can be obtained in different solvents at room temperature. This is accompanied by high contrast changes in fluorescence intensity of the pyrene stopper by the presence of the ferrocenyl moieties on the macrocycle, which quench the emission of pyrene more efficiently with proximity. © 2012 American Chemical Society.

Charge transfer events in semiconducting single-wall carbon nanotubes - Oelsner, Christian; Antonia Herrero, M.; Ehli, Christian; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2011)
Electron-donating ferrocene units have been attached to SWNTs, with different degrees of functionalization. By means of a complementary series of novel spectroscopic techniques (i.e., steady-state and time-resolved), we have documented that mutual interactions between semiconducting SWNT and the covalently attached electron donor (i.e., ferrocene) lead, in the event of photoexcitation, to the formation of radical ion pairs. In the accordingly formed radical ion pairs, oxidation of ferrocene and reduction of SWNT were confirmed by spectroelectrochemistry. It is, however, shown that only a few semiconducting SWNTs [i.e., (9,4), (8,6), (8,7), and (9,7)] are susceptible to photoinduced electron transfer processes. These results are of relevant importance for the development of SWNT-based photovoltaics. © 2011 American Chemical Society.

Es werde Licht ... Absorptionsspektroskopie für die Schule - Ehli, Christian (Chemie Konkret - Forum für Unterricht und Didaktik, 2012)

Facile decoration of functionalized single-wall carbon nanotubes with phthalocyanines via "click chemistry" - Campidelli, Stephane; Ballesteros, Beatriz; Filoramo, Arianna; Diaz Diaz, David; De La Torre, Gema; Torres, Tomas; Rahman, Aminur; Ehli, Christian; Kießling, Daniel; Werner, Fabian; Sgobba, Vito; Guldi, Dirk Michael; et al. (Journal of the American Chemical Society, 2008)
We describe the functionalization of single-wall carbon nanotubes (SWNTs) with 4-(2-trimethylsilyl)ethynylaniline and the subsequent attachment of a zinc-phthalocyanine (ZnPc) derivative using the reliable Huisgen 1,3-dipolar cycloaddition. The motivation of this study was the preparation of a nanotube-based platform which allows the facile fabrication of more complex functional nanometer-scale structures, such as a SWNT-ZnPc hybrid. The nanotube derivatives described here were fully characterized by a combination of analytical techniques such as Raman, absorption and emission spectroscopy, atomic force and scanning electron microscopy (AFM and SEM), and thermogravimetric analysis (TGA). The SWNT-ZnPc nanoconjugate was also investigated with a series of steady-state and time-resolved spectroscopy experiments, and a photoinduced communication between the two photoactive components (i.e., SWNT and ZnPc) was identified. Such beneficial features lead to monochromatic internal photoconversion efficiencies of 17.3% when the SWNT-ZnPc hybrid material was tested as photoactive material in an ITO photoanode. © 2008 American Chemical Society.

Happy Photometry-Tips and Tricks against the Pitfalls when using a School Photometer - Ehli, Christian (Chemie Konkret - Forum für Unterricht und Didaktik, 2020)
With the help of photometry, a large number of scientific projects can be performed at school. In this context, it is recommended to follow a series of experimental parameters. The following article is a help for identification of possible disruptive factors and troubleshooting.
CRIS-Team WoS Importer:2020-08-07

Immobilizing water-soluble dendritic electron donors and electron acceptors - Phthalocyanines and perylenediimides - Onto single wall carbon nanotubes - Hahn, Uwe; Engmann, Sarah; Oelsner, Christian; Ehli, Christian; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2010)
The complementary use of spectroscopy and microscopy sheds light onto mutual interactions between semiconducting single wall carbon nanotubes (SWNT) and either a strong dendritic electron acceptor - perylenediimide - or a strong dendritic electron donor - phthalocyanine. Importantly, the stability of the perylenediimide/SWNT electron donor-acceptor hybrids decreases with increasing dendrimer generation. Two effects are thought to be responsible for this trend. With increasing dendrimer generation we enhance (i) the hydrophilicity and (ii) the bulkiness of the resulting perylenediimides. Both effects are synergetic and, in turn, lower the immobilization strength onto SWNT. Owing to the larger size of the phthalocyanines, phthalocyanine/SWNT electron donor-acceptor hybrids, on the other hand, did not reveal such a marked dependence on the dendrimer generation. Several spectroscopies confirmed that distinct ground- and excited-state interactions prevail and that kinetically and spectroscopically well-characterized radical ion pair states are formed within a few picoseconds. © 2010 American Chemical Society.

Interfacing nanocarbons with organic and inorganic semiconductors: From nanocrystals/quantum dots to extended tetrathiafulvalenes - Katsukis, Georgios; Nieto, Carlos Romero; Malig, Jenny; Ehli, Christian; Guldi, Dirk Michael (Langmuir, 2012)
There is no doubt that the outstanding optical and electronic properties that low-dimensional carbon-based nanomaterials exhibit call for their implementation into optoelectronic devices. However, to harvest the enormous potential of these nanocarbons it is essential to probe them in multifunctional electron donor-acceptor systems, placing particular attention on the interactions between electron donors/electron acceptors and nanocarbons. This feature article outlines challenges and recent breakthroughs in the area of interfacing organic and inorganic semiconductors with low-dimensional nanocarbons that range from fullerenes (0D) and carbon nanotubes (1D) to graphene (2D). In the context of organic semiconductors, we focus on aromatic macrocycles and extended tetrathiafulvalenes, and CdTe nanocrystals/quantum dots represent the inorganic semiconductors. Particular emphasis is placed on designing and probing solar energy conversion nanohybrids. © 2012 American Chemical Society.

Jetzt wird es bunt ... Fotometrische Experimente mit Materialien aus dem Federmäppchen - Ehli, Christian (Chemie Konkret - Forum für Unterricht und Didaktik, 2014)

Manipulating single-wall carbon nanotubes by chemical doping and charge transfer with perylene dyes - Ehli, Christian; Oelsner, Christian; Guldi, Dirk Michael; Mateo-Alonso, Aurelio; Prato, Maurizio; Schmidt, Cordula; Backes, Claudia; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Nature Chemistry, 2009)
Single-wall carbon nanotubes (SWNTs) are emerging as materials with much potential in several disciplines, in particular in electronics and photovoltaics. The combination of SWNTs with electron donors or acceptors generates active materials, which can produce electrical energy when irradiated. However, SWNTs are very elusive species when characterization of their metastable states is required. This problem mainly arises because of the polydispersive nature of SWNT samples and the inevitable presence of SWNTs in bundles of different sizes. Here, we report the complete and thorough characterization of an SWNT radical ion-pair state induced by complexation with a perylene dye, which combines excellent electron-accepting and-conducting features with a five-fused ring-system. At the same time, the perylene dye enables the dispersion of SWNTs by means of- interactions, which gives individual SWNTs in solution. This work clears a path towards electronic and optoelectronic devices in which regulated electrical transport properties are important. © 2009 Macmillan Publishers Limited. All rights reserved.

Screening interactions of zinc phthalocyanine-PPV oligomers with single wall carbon nanotubes - A comparative study - Bartelmeß, Jürgen; Ehli, Christian; Cid, Juan-Jose; Garcia-Iglesias, Miguel; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Journal of Materials Chemistry, 2011)
In this paper, the ability to disperse single wall carbon nanotubes (SWNT) of several different-nature poly(p-phenylene vinylene) (PPV) oligomers having pendant zinc phthalocyanines (ZnPc) has been investigated. Based on the quenching of the ZnPc and SWNT fluorescence in the supramolecular assemblies, it has been shown that parameters such as p/n-type character of the oligomer, size and the distance between the ZnPc moiety and the conjugated backbone play an important role in the strength of the interactions. Important results suggest that n-type oligomers as well as certain flexibility in the phthalocyanine arrangement are breakthroughs for immobilizing SWNT in THF, affording stable and homogeneous suspensions. Transient absorption measurements confirm that upon photoexcitation the photoexcited ZnPc triggers an intraensemble charge transfer to yield oxidized ZnPc and reduced SWNT. © 2011 The Royal Society of Chemistry.

Tetrathiafulvalene-based nanotweezers-noncovalent binding of carbon nanotubes in aqueous media with charge transfer implications - Romero, Carlos; Garcia, Raul; Herranz, M. Angeles; Ehli, Christian; Ruppert, Michaela; Hirsch, Andreas; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2012)
Electron donor-acceptor hybrids based on single wall carbon nanotubes (SWCNT) are one of the most promising functional structures that are currently developed in the emerging areas of energy conversion schemes and molecular electronics. As a suitable electron donor, π-extended tetrathiafulvalene (exTTF) stands out owing to its recognition of SWCNT through π-π stacking and electron donor-acceptor interactions. Herein, we explore the shape and electronic complementarity between different types of carbon nanotubes (CNT) and a tweezers-shaped molecule endowed with two exTTFs in water. The efficient electronic communication between semiconducting SWCNT/multiwall carbon nanotubes (MWCNT), on one hand, and the water-soluble exTTF nanotweezers 8, on the other hand, has been demonstrated in the ground and excited state by using steady-state as well as time-resolved spectroscopies, which were further complemented by microscopy. Importantly, appreciable electronic communication results in the electronic ground state having a shift of electron density, that is, from exTTFs to CNT, and in the electronic excited state having a full separation of electron density, that is oxidized exTTF and reduced CNT. Lifetimes in the range of several hundred picoseconds, which were observed for the corresponding electron transfer products upon light irradiation, tend to be appreciably longer in MWCNT/8 than in SWCNT/8. © 2012 American Chemical Society.

Tuning and optimizing the intrinsic interactions between phthalocyaninebased PPV oligomers and single-wall carbon nanotubes toward n-type/p-type - Bartelmeß, Jürgen; Ehli, Christian; Cid, Juan-Jose; Garcia-Iglesias, Miguel; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Chemical Science, 2011)
In this work we have developed a strategy to immobilize functional groups such as ZnPc onto the surface of SWNT without, however, the needs of covalent functionalization, using substituted PPVoligomers (1-4) with different electronic character. The complementary use of a series of microscopies and spectroscopies is central, especially to gather a comprehensive picture of the mutual interactions. Importantly, only 1, bearing electron-withdrawing CN substituents, interacts tightly with SWNT affording stable and finely dispersed SWNT suspensions. 2-4, on the other hand, fail to disperse SWNT in THF following our newly developed protocol. A likely rationale is the p-type character of PPVoligomers 2-4, which imposes repelling forces relative to p-type SWNT, while placing CN groups yields n-type PPV-oligomer 1 and, in turn, strengthens the π-π interactions with SWNT. Photoexcitation of SWNT/1 hybrids generates a metastable radical ion pair state, namely oxidized ZnPc and reduced SWNT. Quite remarkable is the ratio of charge separation to charge recombination, namely nearly 3 orders of magnitude, which is encouraging to fabricate photovoltaic cells that are based, for example, on different nanocarbons. © The Royal Society of Chemistry 2011.